FINANCING PATTERN AND ECONOMIC ANALYSIS OF FISH CULTIVATION BUSINESS USING FLOATING CERAMBA MEDIA IN BULUHCINA VILLAGE, SIAK HULU DISTRICT, KAMPAR DISTRICT, RIAU - Chicka Willy Yanti; Yudho Harjoyudanto; Andri Hendrizal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Fish farming using KJA media is quite developed in Buluhcina village. The development of KJA cultivation in Buluhcina Village affects the socio-economic aspects of the community. Every economic activity carried out by fish cultivators using KJA media is expected to be profitable and sustainable. The problem in this research is whether the activities that have been carried out so far actually generate benefits for cultivators and the business being carried out is feasible to develop. For this reason, this research needs to be done to see how the financing and economic patterns of aquaculture with KJA media. By using the quantitative descriptive analysis method, the conclusions are obtained, namely: The investment requirement for fish farming using KJA media is IDR 9,025,000 with the largest amount of investment being for timber procurement of IDR 5,675,000; The financing pattern for fish farming using KJA media shows a total financing of IDR 21,027,500, where the largest cost incurred is the cost of providing feed of IDR 7,425,000; Net income or profit obtained from fish farming using KJA media is IDR 23,522,500; The R / C ratio value is 2.11 which indicates that the fish farming business using KJA media is included in the business category that is feasible to be developed. The R / C ratio value of 2.11 means that every Rp. 1, - that is issued will get an income of Rp. 2.11, - The payback period value or the value of the ability to return investment from fish farming with KJA media is 0.38 which indicates that the cultivation business fish using KJA media are able to return the amount of investment invested in a period of 0.38 years or ± 4 months only. The ROI value or the return on business ratio is 2.60, which means that every investment of Rp. 1, - will provide a profit or profit of Rp. 2.60,-